The role of physical literacy in improving fitness and active lifestyle - Apriliyanto, Rizki; Hardovi, Bahtiar Hari; Sulaiman, Ahmad (Journal Sport Area, 2025)
Background: Physical literacy is one of the main concepts that encompasses a wide range of outcomes and themain focus of the physical education curriculum. In designing physical literacy, it takes very serious concern, whether sports education students are ready in implement experiential learning programmes that contribute to improvement physical literacy, daily lifestyle, and pedagogic abilities. Considering the importance of physical literacy for students, future physical education teacher candidates should have a good level of understanding of physical literacy before passing it on to their students in the future. Research Objectives: This study aims to determine the understanding of physical literacy in sports education students. Methods: A descriptive quantitative approach was adopted for this study. During the course of this study, closed-ended questionnaire were used to collect data. The population in this study was sports education students of Muhammadiyah University of Jember. The sampling technique was voluntary response sampling, totalling 217 students aged between 18-23 years, divided into 194 male students and 36 female students. An alternative in choosing answers to questionnaires with a Likert scale of 1-5 (1: strongly disagree to 5: strongly agree) then the data was analysed using percentages. Finding and Results: Sport education students have a high perception of physical literacy mainly related to the health-related benefits of exercise. But there is still a small proportion of them do not have self-management skills for fitness. A total of (82.1%) of them realized that the benefits of exercise can improve fitness. Conclusion: Sports education students’ good understanding of physical literacy should be accompanied by good fitness management skills as a form of implementation of this understanding. As future physical education teachers, they will be role models for their students. The relationship between an active lifestyle between physical education teachers and students is an interesting recommendation for further research.